An apparatus for the measurement of tensile creep and contraction ratios in small non-rigid specimens - Darlington, M. W.; Saunders, D. W. (College of Aeronautics)
An apparatus is described for precise measurement of creep properties in specimens with gauge lengths down to 1.2 cm. An extensometer has been developed which is supported independently of the specimen and exerts a load on the specimen of less than 5 grams. It can thus be used with small non-rigid specimens. The extensometer will detect strains down to 2 x 10-6. The stability is excellent. An adaptation of the system which allows simultaneous measurement of tensile strain and lateral strain during creep is also described. The apparatus was designed for the measurement of anisotropy of creep properties in oriented thermoplastics and reference to such measurements is given. It is however entirely suitable for general application to small specimens.